2005
DOI: 10.1177/0022487104272709
|View full text |Cite
|
Sign up to set email alerts
|

“Nadie Me Dijó [Nobody Told Me]”

Abstract: Nationwide and statewide shifts and ambiguity in language education policy have created substantial instability for teachers. Through a cross-case study and analysis of bilingual teachers in two states, this article shows how these teachers participate in responding to and making decisions regarding language policy. This article shows how and why an understanding of language policy and the decision making involved with it is a crucial dimension of the professional roles of teachers who have second-language lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In alignment with previous research on language teacher agency (e.g., Molina, 2017;Ollerhead, 2012;Tao & Gao, 2017;Varghese & Stritikus, 2005), our findings provide support for the conceptualization of agency as phenomenon/doing (Priestley et al, 2015). That is to say, it was found that agency was achieved as a result of the interplay of the teachers' "individual efforts, available resources, and contextual and structural factors, as they come together in particular and, in a sense, always unique situations" (Biesta & Tedder, 2007, p. 137).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In alignment with previous research on language teacher agency (e.g., Molina, 2017;Ollerhead, 2012;Tao & Gao, 2017;Varghese & Stritikus, 2005), our findings provide support for the conceptualization of agency as phenomenon/doing (Priestley et al, 2015). That is to say, it was found that agency was achieved as a result of the interplay of the teachers' "individual efforts, available resources, and contextual and structural factors, as they come together in particular and, in a sense, always unique situations" (Biesta & Tedder, 2007, p. 137).…”
Section: Discussionsupporting
confidence: 90%
“…Accumulating evidence has provided support for the agency-as-phenomenon/doing conceptualization; both teachers' current environments and their past experiences contribute to shaping, constraining, and enabling teacher agency (e.g., Lipponen & Kumpulainen, 2011;Varghese & Stritikus, 2005). However, previous research on this topic has also pointed to a wide range of ways in which teacher agency manifests itself, depending on the exigencies of particular situations and the individuals involved.…”
Section: Teacher Agencymentioning
confidence: 99%
“…Classroom teachers, especially those new to international schools, may succumb to feelings of being overwhelmed due to their lack of training in working with English language learners (Walker, Shafter, & Iiams, 2004) or lack of organizational support (Varghese & Stritikus, 2005). Some teachers in schools with a formal written language policy may not follow the policy consistently because they disagree with the language policy or make decisions based on their understandings (Duggan, 2017;Throop, 2007;Varghese & Stritikus, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although the policy may be implemented, the implementation of a policy does not guarantee understanding and compliance (Darling-Hammond, 1990;Duggan, 2017;García & Menken, 2010;Shohamy, 2006). Additionally, school language policies are sometimes ambiguous and may lack specific details that can lead to stakeholder understanding (Lehman, 2017;McClelland, 2001) or require teacher interpretation of the policy (Duggan, 2017;Timberlake, 2020;Varghese & Stritikus, 2005). Lastly, because power imbalances exist within many schools (Carder, 2013), language policies that specify roles can avoid confusion and alleviate power imbalances often experienced by ESL/EAL/ELD/TESOL specialist teachers.…”
Section: Language Policymentioning
confidence: 99%
“…In the end, such concerns are never entirely allayed through state-authored measures. A significant responsibility falls to educators, particularly language teachers, to straddle these tensions, including those heightened through changes in educational policy (e.g., Clemente, 2009;Varghese & Stritikus, 2005), to negotiate a language pedagogy that averts attrition of a minority language while introducing a lingua franca that might prove useful to disenfranchised students in their future endeavours (Canagarajah, 1999;Kamwangamalu, 2005). In presenting our study's findings, we shall see how professional educators exercised their agency as stakeholders in a subaltern, indigenous context as they negotiated the tensions between the minority (Mayo), majority (Spanish), and global (English) varieties as they carried out their responsibilities as multilingual educators.…”
Section: Theoretical Framework and Research Precedentsmentioning
confidence: 99%